Endophytic Mycoflora as a Source of Biotherapeutic Compounds for Disease Treatment - Ravindra Prasad Aharwal, Suneel Kumar, Sardul Singh Sandhu (Journal of Applied Pharmaceutical Science, 2016)
Endophytic mycoflora are ubiquitous organisms residing in the internal tissues of the plants, at least for a portion of their lives without causing apparent symptoms of infection. Endophytes serve as rich sources of novel natural compounds with a wide-spectrum of biologically active agents. This review reveals the significance of endophytic mycoflora from plants as sources of bioactive organic compounds. The bioactive compounds produced by endophytic fungi originate by various biosynthetic pathways like PKS/NRPS. These compounds belong to diverse structural groups such as alkaloids, benzopyranones, chinones, cytochalasines, depsipeptides, enniatines, flavonoids, furandiones, isocumarines, peptides, polyketones, phenols, quinols, terpenoids, tetralones and xanthones were characterized by NMR, mass spectrometry, X-ray crystallography etc. Therefore, endophytes, represent a chemical reservoir for array of new compounds which are anti-cancerous, anti-microbial, anti-diabetic, anti-oxidant, anti-parasitical, anti-viral, anti-mycobacterium, anti-insecticidal, anti-malarial, anti-biotic, immunosuppressive & immunomodulatory agents, also in addition, other compounds were used in pharmaceutical and agrochemical industries. This paper mainly focuses on the exploration of novel and useful compounds from endophytic mycoflora, and study of their roles in cure of diseases, the recent scenario of screening approach for novel drugs and their pharmacological interest.
Keywords: Endophytic Mycoflora, Infectious diseases, Secondary metabolites, Drug resistance.